2011
DOI: 10.1007/s10493-011-9442-8
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of tortoise tick Hyalomma aegyptium under laboratory conditions

Abstract: The tortoise tick Hyalomma aegyptium has a typical three-host life-cycle. Whereas its larvae and nymphs are less host-specific feeding on a variety of tetrapods, tortoises of the genus Testudo are principal hosts of adults. Ticks retained this trait also in our study under laboratory conditions, while adults were reluctant to feed on mammalian hosts. Combination of feeding larvae and nymphs on guinea pigs and feeding of adults on Testudo marginata tortoises provided the best results. Feeding period of females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The present work revealed that H. rufipes had a complete life cycle of 179 days on average under laboratory conditions, which was longer than those of H. asiaticum kozlovi, H. impeltatum, H. detritum, H. aegyptium and H. dromedarii (Alahmed and Kheir 2003;Chen et al 2009;Logan et al 1989;Ouhelli 1994;Š iroký et al 2011). The egg incubation period was the longest in the life cycle of H. rufipes.…”
Section: Discussionmentioning
confidence: 44%
“…The present work revealed that H. rufipes had a complete life cycle of 179 days on average under laboratory conditions, which was longer than those of H. asiaticum kozlovi, H. impeltatum, H. detritum, H. aegyptium and H. dromedarii (Alahmed and Kheir 2003;Chen et al 2009;Logan et al 1989;Ouhelli 1994;Š iroký et al 2011). The egg incubation period was the longest in the life cycle of H. rufipes.…”
Section: Discussionmentioning
confidence: 44%
“…These parasites may cause serious problems by distributing pathogens among animal owners and animals (2,24). Among Hyalomma type ticks, Hyalomma aegyptium is known as the tortoise tick due to its specificity to tortoises on which mature forms of ticks live (15,27,29). This specificity is sometimes so high that it has caused that the presence of H. aegyptium is considered as an indirect indicator of the presence of Testudo graeca (28,30).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…Hyalomma aegyptium (Linnaeus, 1758) is a three-host tick and has an extremely long feeding period compared to most of the other tick species [7]. All stages, but especially adults, are highly host-specific and feed primarily on tortoises.…”
Section: Introductionmentioning
confidence: 99%